“La rendición de cuentas a través del uso de boletas falsas en el delito de peculado” - Galvez Moncada, Oscar Esteban (2019)
ABSTRACT In the present investigation, which is entitled "Accountability through the use of false ballots in the crime of peculado", deals with the problem that, if accountability with the presentation of bags that are not truthful, may constitute an act of the crime of embezzlement. For this it is raised as a hypothesis that does not constitute a peculado crime, whereas the Peruvian Penal Code establishes such an offence as the conduct in which the server misappropriates public funds that were given to him in administration, perception or custody, whereas the allowances provided do not fall within these possibilities. For this purpose, the general objective is to determine whether accountability through the use of false ballots to support unrealized expenses is a pecuniary offence, contrasting the hypothesis with the theoretical dispersion of the crime in analysis, as well as the methodological application of the universal method, as well as the general method covering the deductive and inductive methods, and the specific method, generating with it, a revision from multiple sides, on the problematic put to the interpretative one. Finally, it is concluded from the development of this investigation that Accountability through false documents is not a crime of embezzlement, but of using false documents; likewise it was concluded that the majority of dogmatic, as well as of the study of jurisprudence, are inclined not to consider these behaviours as proper to the crime of peculado.